2007
DOI: 10.1097/mou.0b013e32802b7081
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical nephroureterectomy for transitional cell carcinoma: where are we in 2007?

Abstract: Findings over the past 2 years show both the continued progress of LNU and the need for further evolution to optimize patient morbidity and oncologic outcomes. As laparoscopic training is integrated into urologic residency programs, standardizing the variables within LNU will be paramount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nephroureterectomy with the removal of the bladder cuff, mainly comprising open nephroureterectomy (ONU) and laparoscopic nephroureterectomy (LNU), is currently the ‘gold standard’ treatment for upper tract TCC [1–3]. LNU has been performed increasingly for surgically treating upper tract urothelial cancer because it is minimally invasive, safe and effective [4,5]. LNU has also been reported to be equivalent to ONU in margin‐free rates, rates of local recurrence and metastases and cancer‐specific survival rates after surgery [6,7]; however, controversy still exists about the best method for managing the distal ureter and bladder cuff during the laparoscopic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Nephroureterectomy with the removal of the bladder cuff, mainly comprising open nephroureterectomy (ONU) and laparoscopic nephroureterectomy (LNU), is currently the ‘gold standard’ treatment for upper tract TCC [1–3]. LNU has been performed increasingly for surgically treating upper tract urothelial cancer because it is minimally invasive, safe and effective [4,5]. LNU has also been reported to be equivalent to ONU in margin‐free rates, rates of local recurrence and metastases and cancer‐specific survival rates after surgery [6,7]; however, controversy still exists about the best method for managing the distal ureter and bladder cuff during the laparoscopic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Hattori et al reported a significantly decreased number of lymph nodes removed following LNU (8.2–11.6) as compared to ONU (16.5) [44]. Busby and Matin, however, reported their experience that removal of an equivalent number of nodes could be performed with both laparoscopic and open approaches [58]. …”
Section: Role Of Lymphadenectomymentioning
confidence: 99%